Stress Response of Vibrio parahaemolyticus and Listeria monocytogenes Biofilms to Different Modified Atmospheres - Qian, Hui; Li, Wei; Guo, Linxia; Tan, Ling; Liu, Haiquan; Wang, Jingjing; Pan, Yingjie; Zhao, Yong (Frontiers in Microbiology, 2020)
The sessile biofilms of Vibrio parahaemolyticus and Listeria monocytogenes have increasingly become a critical threat in seafood safety. This study aimed to evaluate the effects of modified atmospheres on the formation ability of V. parahaemolyticus and L. monocytogenes biofilms. The stress response of the bacterial biofilm formation to modified atmospheres were illuminated by determining the live cells, chemical composition analysis, textural parameters changes and the expression of regulatory genes, etc. Results showed that the biofilms formation ability of V. parahaemolyticus was efficiently decreased, supported by that the modified atmospheres significantly reduced the key chemical composition (extracellular DNA and proteins) of extracellular polymeric substance (EPS) and negatively altered the architectural structural parameters (biovolume, thickness and bio-roughness) of biofilms during the physiological conversion from anaerobiosis to aerobiosis. While, the modified atmospheres treatment increased the key chemical composition of EPS and the architectural structural parameters of L. monocytogenes biofilms from anaerobiosis to anaerobiosis. Meanwhile, the expression of biofilms formation genes (luxS, aphA, mshA, oxyR and opaR), EPS production genes (cpsA, cpsC and cpsR) and virulence genes (vopS, vopD1, vcrD1, vopP2β and vcrD2β) of V. parahaemolyticus was down-regulated. For the L. monocytogenes cells, the expression of biofilms formation genes (flgA, flgU and degU), EPS production genes (Imo2554, Imo2504, inlA, rmlB) and virulence genes (vopS, vopD1, vcrD1, vopP2β and vcrD2β) was up-regulated during the physiological conversion. All these results indicated that the modified atmospheres possessed significantly different regulation on the biofilms formation of Gram-negative V. parahaemolyticus and Gram-positive L. monocytogenes, which will provide a novel insight to unlock the efficient control of Gram-negative and Gram-positive bacteria in modified atmosphere packaged food.